The Quality of Science Education: Viewpoints of Secondary School Science Teachers - Jhovel Roy Calo; Mercy De Vera (Journal of Research in Education and Pedagogy, 2025)
In today’s world, the success of a society is increasingly tied to its ability to cultivate a scientifically literate population. Yet, many nations struggle to provide a solid foundation in science education, especially in under-privileged regions. Science education plays a crucial role in shaping the future of societies by fostering critical thinking, innovation, and scientific literacy among students (DepEd, 2020). This qualitative research study explores the perceptions of secondary school science teachers regarding the current state of science education in the Philippines, specifically focusing on the province of Bukidnon. The primary objectives of the study are to understand teachers’ viewpoints on science education, identify significant barriers that hinder quality instruction, and propose actionable solutions to these challenges. The thematic analysis of the data reveals a notable increase in student interest and engagement, driven by factors such as rising enrollment in STEM programs and active participation in science fairs. Despite these positive trends, ongoing concerns about teacher quality, inadequate resources, and outdated curricula continue to impede effective science instruction in the classroom. Key barriers identified include insufficient teacher preparation, foundational gaps in student comprehension, and constraints on resources, such as limited access to laboratory activities and essential equipment. The findings emphasize the pressing need for program restructuring, the early introduction of science concepts, and the integration of prerequisite courses designed to enhance the overall effectiveness of science education programs. These recommendations aim to better equip future science educators and foster a more conducive learning environment. Ultimately, this research contributes valuable insights to ongoing efforts aimed at improving science education in the Philippines, underscoring the necessity of addressing systemic issues to promote a more effective, equitable, and enriching educational experience for all students.